(untitled) - Sustekova, Daniela (Doprava a spoje, 2009)
In this article there are described the using possibilities of computer nets WLAN, especially WI-FI nets in the road transport. There is described a concrete realization of this utilization with the functions description using the radio transmission medium WI-FI and Bluetooth as well as the benefits of this realization.